Agent‐based decentralised load flow computation for smart management of distribution system. Issue 3 (1st February 2017) - Saxena, Kritika; Abhyankar, Abhijit R.
Abstract : Centralised operation of distribution system suffer from inherent difficulties like increased complexities with increased system size, consequent frequent upgradation, delayed decision making and so on. Paradigm shift towards decentralised operations overcomes the aforesaid problems and assist in automated grid operations. Load flow is an indispensable tool, where the system operator does centralised calculation of state variables. This study proposes a novel approach towards decentralised load flow computation for weakly meshed distribution system. Agent technology is employed to design the framework which is based on agent relaying concept. The agents are located on system buses, and have limited access to information pertaining to system topology and nodal injections. By coordinating with neighbouring agents, they aim towards the fulfilment of their own goal, i.e. bus voltage calculation. To achieve this, several behaviours such as forward sweep, backward sweep, break point calculations and scenario generation are incorporated in the proposed system design. The solution thus obtained is decentralised in nature. The agent designing is done under JAVA environment on JADE platform. Two case studies considering 15 bus and 69 bus radial distribution systems are simulated with the proposed concept to show the validity and applicability of the proposed framework for smart grid management systems.